Operating characteristics and energy efficiency of heat pump dryer for industrial electroplating sludge drying - Chin, Yen Wei (2023)
Conventionally, an electroplating coating factory would handle its process sludge waste from discharge point source until the dewatering stage only. Huge amount of dewatered sludge cake would incur high hidden cost to the production particularly in sludge transportation, storage and disposal. Therefore, further reduction of moisture content in the sludge after dewatering stage is essential in order to diminish the sludge handling cost. Nonetheless, the energy cost for sludge drying must be justifiable and low enough to take the advantage of it. An energy efficient sludge drying technology is indeed greatly in need. Heat pump dryer is known to be energy efficient due to its ability of heat recovery. Therefore, in the present study, a pilot-scale heat pump dryer was developed to evaluate the potential of heat pump dryer in sludge drying. Experiments were conducted to determine the drying characteristics and energy efficiency under drying temperature of 35°C-50°C and air humidity of 10%RH-52%RH. Comparisons were made against samples from conventional hot air drying (35°C-70°C). Results revealed that the drying rate would increase in proportion to wet bulb depression of drying air, where the highest effective diffusivity was recorded at 1.09765 x 10-8 m2/s in heat pump drying at 50°C. Due to the dehumidification function of heat pump dryer, when under same drying temperature, drying air in heat pump dryer would possess higher wet bulb depression as compared to hot air dryer. Therefore, drying rates of heat pump dried samples were higher than hot air dried samples.